TINGKAT MINAT BACA MAHASISWA DI PROVINSI BANTEN - Diana Romdhoningsih; Rizky Nur Pratama; Farhatul Ain (Prakata: Jurnal Bahasa dan Sastra Indonesia Serta Pembelajaran, 2024)
It can be said that students' reading interest in Banten is still very low, this can be seen from the public literacy index which is only 3.1%. That is, when there are 100 adults there are only 3.1 people who have the habit of reading more than 4 hours/day. The purpose of this study was to describe the relationship between students' reading interest and the quality of an area, both in the fields of science and technology, as well as the civilization of the area. The research method is qualitative by conducting in-depth interviews and participatory observations. The results showed that the reading interest of students at several universities in Banten was still low, this was due to many internal and external factors. Internal factors are more due to interest, curiosity, and desire to move forward. External factors are more influenced by friends, parental guidance, environment and others